Nauchno-metodicheskie problemy sportivnykh edinoborstv - Novikov, A. A. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this paper was to consider the influence of sports science on the contemporary theory and methodology of sports training. The author analyzes the scientific activities of specialist on single combats working in All-Russian research institute of physical culture for the last 35 years. The main directions of works performed by its specialists are considered. The principal methodological positions of that scientific team are substantiated and described. The methods and organization of researches are shown.